This is not an article: something discussing the creative process of Kritik der Oberfläche - Oliveira, Victor Afonso Wanderley de; Gazoni, Bruno (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2025)
Adorno states that music ”is a language, but without concepts.” This article documents the creative process behind the piece Kritik der Oberfläche, yet it does not engage in any conceptual discussion of that process. This omission is intentional: it is carried out by the main composer itself—ChatGPT. What we present here is a report of the encounter between the researchers and the model, as we prompted it to engage with Adorno’s concept and to compose three musical structures based on that engagement— mirroring how music researchers often discuss concepts connected to their own music in academic writing. After feeding the model with the necessary context, we prompted it to develop a discussion around Adorno’s notion. Next, we prompted it to generate its own musical prompts to be actionable by any large language models (LLMs), based on that conceptual discussion, in a Chain-of-Thought[1] manner. Finally, we prompted the model to create SuperCollider[2] patches for each of the generated prompts and to comment on how each one is expressed in the programming. The resulting musical fragments of this process were then assembled together in SuperCollider, resulting in the final piece.